Interaction of the BELL-like protein ATH1 with DNA: Role of homeodomain residue 54 in specifying the different binding properties of BELL and KNOX proteins - Viola, Ivana Lorena (2006)
We have studied the interaction of the BELL-like Arabidopsis homeodomain protein ATH1 with DNA. Analysis of oligonucleotides selected by the ATH1 homeodomain from a random mixture suggests that ATH1 preferentially binds the sequence TGACAGGT. Single nucleotide replacements at positions 2 or 3 of this sequence abolish binding, while changes at position 4 are more tolerated. Changes outside this core differentially affect binding, depending on the position. Hydroxyl radical footprinting and missing nucleoside experiments showed that ATH1 interacts with a 7-bp region of the strand carrying the GAC core. On the other strand, protection was observed over a 7-bp region, comprising one additional nucleotide complementary to T in position 1. A comparative analysis of the binding preferences of the homeodomains of ATH1 and STM (a KNOX homeodomain protein) indicated that they bind similar sequences, but with differences in affinity and specificity. The decreased affinity displayed by the ATH1 homeodomain correlates with the presence of valine (instead of lysine as in STM) at position 54. This difference also explains the decreased and increased selectivities, respectively, at positions 4 and 5. Our results point to an essential role of residue 54 in determining the different binding properties of BELL and KNOX homeodomains.